Reevaluating BED in cervical cancer HDR brachytherapy: source decay and tissue-specific repair significantly impact radiobiological dose - Bi, Suyan; Zhou, Jiaomei; Xu, Meiling; Dai, Zhitao (Frontiers in Oncology, 2025)
ObjectiveThis study aims to investigate the influence of intrafraction DNA damage repair on biologically effective dose (BED) in Ir-192 high-dose-rate (HDR) brachytherapy (BT) for cervical cancer. Specifically, we examine BED variations resulting from source decay at various treatment time points across different tumor cell lines and normal tissues.MethodsInstead of the simplified BED formula, which does not account for intrafraction and interfraction repair or tumor repopulation, we applied the generalized BED (BEDg) formula. BED values for various subtypes of cervical cancer tissues and Organs at Risk (OARs) were calculated using both BED formulas across a full source exchange cycle.ResultsThe results demonstrate that BEDg values are significantly lower and decrease more markedly and extended treatment time compared to BED values. For tumors with α/β = 10, the maximum BED deviation (ΔBED = BED − BEDg) reached 3.05% ± 0.47% at D90% of the High-Risk Clinical Tumor Volume (HRCTV) in BT. For specific cervical cancer subtypes, the three largest ΔBED (%) values at D90% of HRCTV were 14.06 ± 1.67 (stages I–II, α/β = 10), 9.92 ± 1.19 (HX156c, α/β = 16.46), and 7.57 ± 1.05 (HX155c, α/β = 11.40). Similar trends were observed in OARs. As the source decays, the maximum ΔBED (%) at D0.1cc was 13.37 ± 2.27 (bladder), 11.92 ± 2.10 (rectum), 12.45 ± 2.27 (sigmoid), and 11.91 ± 2.62 (small intestine), assuming α/β = 3.ConclusionsThese findings confirm that source decay significantly impacts BED in cervical cancer treatment, affecting both tumor tissues with varying radiosensitivities and normal tissues. The simplified BED formula tends to overestimate the actual dose, especially at a source activity of 2 Ci, highlighting the necessity of using the full BEDg model for accurate dosimetric evaluation in HDR brachytherapy.